1970
DOI: 10.1136/ard.29.6.591
|View full text |Cite
|
Sign up to set email alerts
|

Mode of aggregation of hyaluronic acid protein complex on the surface of articular cartilage.

Abstract: There is a great deal of experimental evidence that the frictional forces between sliding cartilage surfaces lubricated with synovial fluid are very low under normal conditions. Considering coefficient of friction as the meaningful measure of friction (i.e. tangential force resisting sliding divided by the normal load forcing the sliding surfaces together), typical values for cartilage on glass have been found to be 0-002 to 0-01 (McCutchen, 1962; Walker, 1969). A similar range was found for the ankle joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…In fact several investigators proposed that, contrary to McCutchen’s weeping hypothesis, the synovial fluid trapped between the cartilage surfaces would undergo ultrafiltration whereby its water solvent and small molecular weight solutes would flow into the porous cartilage, leaving behind a hyaluronic acid gel that might act as a boundary lubricant (Longfield et al, 1969; Maroudas, 1967; Walker et al, 1968; Walker et al, 1970). This alternative mechanism was called ‘boosted lubrication’ (Longfield et al, 1969; Walker et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…In fact several investigators proposed that, contrary to McCutchen’s weeping hypothesis, the synovial fluid trapped between the cartilage surfaces would undergo ultrafiltration whereby its water solvent and small molecular weight solutes would flow into the porous cartilage, leaving behind a hyaluronic acid gel that might act as a boundary lubricant (Longfield et al, 1969; Maroudas, 1967; Walker et al, 1968; Walker et al, 1970). This alternative mechanism was called ‘boosted lubrication’ (Longfield et al, 1969; Walker et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators (McCutchen, 1962;Walker et al, 1970; Mow and Lai, 1979a) examined the friction between small sections of synovial joint surfaces and glass, while others used rubber, glass, and metal surfaces in various configurations as analogues for particular aspects of synovial joint lubrication (McCutchen, 1966;Higginson and Norman, 1974a;Davies et al, 1979). This research involving artificial surfaces assisted in developing an understanding of the various lubrication mechanisms which could act in synovial joints.…”
Section: Introductionmentioning
confidence: 99%
“…As the water is "wrung out", this effect is diminished and the friction coefficient would increase, as he observed experimentally. Conversely, Walker et al [16,22], Dowson et al [23], and Longfield et al [24] attributed the observed time-dependent frictional response to a mode of lubrication which they called "boosted lubrication". In their analysis, approaching cartilage surfaces would trap pools of concentrated synovial fluid within the "valleys" as "peaks" on opposing surfaces come into contact.…”
Section: Introductionmentioning
confidence: 99%